Making History Relevant In 21st Century: An Indian Perspective - Bohet, Dr. Ajit Kumar; Dash, Rashmi Rekha (Voices of Teachers and Teacher Educators, 2022)
The general perception among the students, teachers, guardians and all stakeholders is that History is a non-utility subject, and that it is irrelevant in respect to providing career opportunities in general, and job prospects in particular. It has been felt that while the yardstick for giving a judgment on the aspect of ‘Relevance’ of a subject in the marketoriented world of the 21st century largely depends on its potential towards providing pecuniary benefits, but there are other attributes which can be considered as benchmarks for determining the utility aspect of a subject. And the most striking of them is the role of the subject in presenting a platform for providing ‘Competency-based Learning’, which has assumed a significant dimension after the declaration of the National Education Policy 2020. The paper takes into account the indicators of quality education and examines them in the light of teaching History at the senior secondary level, where a key component is activity-based learning targeted towards development of the spirit of inquiry, and it thus establishes the relevance of the subject in the 21st century.